Occurrence of obesity and risk of obstructive sleep apnoea syndrome in adult patients presenting for elective surgery at an academic hospital - Naidoo, Kamini (My University, 2016)
Background: Worldwide obesity has more than doubled since 1980 and is the fifth leading cause of death (1). Obesity is a risk factor for the occurrence of obstructive sleep apnoea syndrome (OSAS) (2). The incidence of OSAS in the USA is reported to be between 9 to 26% with the incidence in the surgical population reportedly being higher (3, 4). Obesity and OSAS have implications for the anaesthetic management of patients. It is important for the anaesthesiologist to know the occurrence of obesity and risk of OSAS in the patient population presenting for surgery (5, 6). Aim: The aim of this study was to describe the occurrence of obesity and risk of OSAS in adult, elective surgery patients at an academic hospital. Method: A descriptive, contextual, prospective study design was used. The height, weight, used to calculate the BMI, and neck circumference, used as part of the STOPBANG questionnaire, were taken by the researcher. The STOP-BANG questionnaire was used to assess for risk of OSAS in all patients. Results: The study included 250 patients of which 153 (61%) were female and 97 (39%) were male. There were 223 (89.2%) black patients, 15 (6.0%) coloured, 10 (4.0%) white and 2 (0.8%) Indian patients. Of these patients 81 (32.4%) had a BMI of ≥ 30 (95% CI 26.6- 38.2%) and were classified as obese. There were 69 (45.1%) obese females and 12 (12.4%) obese males. A STOP-BANG score of < 3 was attained by 205 (82%) patients and ≥ 3, indicating a risk for OSAS, by 45 (18%) patients of which 22 (48.9%) had a BMI of < 30 and 23 (51.1%) a BMI ≥ 30. Chi-square tests revealed statistically significant relationships between obesity and gender with a lower BMI being associated with being male (χ2 [1] = 29.03, p = 0.001), and age younger than 40 years (χ2 [1], p = 0.001). Chi-square tests revealed statistically significant relationships between BMI and risk of OSAS, with lower risk being associated with a lower BMI (p = 0.003). A lower risk of OSAS was also associated with being female (p = 0.004) and a higher risk of OSAS was associated with being ≥ than 40 years of age (p = 0.001). Conclusion: Obesity is a multi systemic disease which carries significant morbidity and mortality.It is not only important to identify the disease but also to grade its severity and assess the degree of dysfuction it has caused so that the patient can be optimally assessed by the anaesthetist. Our study showed a occurrence of obesity of 32.4% which was comparable with the highest prevalences in the world. This should however be intepreted with caution as the study may not be generalisable to other communities. OSAS too is associated with a higher morbidity and mortality. It goes undiagnosed or under-diagnosed in a large proportion of patients, and poses increased anaesthetic risk. It should be screened for and identified as well as it’s severity graded in order to institute appropriate anasthetic management and make plans for post operative care in a specialised environment. The risk of OSAS was found to be 18% in our study. It was found to be higher in males, and age older ≥ 40. Although there was a high occurence of obesity in the females there was a lower risk of OSAS. The risk of OSAS was similar in obese and non obese patients.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology Johannesburg, 2015